Information-led Policing: Non-Profit Organization’s Terrorist Financing - Wang, Shacheng (International journal of offender therapy and comparative criminology, 2024)
In order to prevent and fight terrorism, a new research area has developed called terrorist financing. An important aspect is the financing of terrorism by Non-Profit Organization (NPO), through transfer funds, terrorist alliances, abuse of NPOs, terrorist recruitment, and false NPOs and agents. Therefore, the NPO counter-terrorist financing strategy was established, considering four major aspects: warning information indicators, internal management mechanisms, international cooperation and information sharing, and counter-terrorist Financing legislation. This paper provides a new way to supervise the terrorist financing of NPOs. First, actual cases should be collected, and viable warning indicators for regulatory agencies and NPOs should be established. Second, internal management mechanisms should be strengthened to actively prevent terrorist activities within NPOs. Third, given the global activity of NPOs and terrorist organizations, information-led international cooperation must be emphasized. Fourth, from the angle of independent counter-terrorist Financing legislation, the gap should be filled in NPO counter-terrorist Financing legislation.